International handbook of research on environmental education - Stevenson, Robert (New York : Routledge, 2013)
"The environment and contested notions of sustainability are increasingly topics of public interest, political debate, and legislation across the world. Environmental education journals now publish research from a wide variety of methodological traditions that show linkages between the environment, health, development, and education. This growth in scholarship makes this an opportune time to review and consolidate the knowledge base of the environmental education (EE) field. The purpose of this 51-chapter handbook is not only to illuminate the most important concepts, findings and theories that have been developed by EE research, but also to critically examine the historical progression of the field, its current debates and controversies, what is still missing from the EE research agenda, and where that agenda might be headed. Published for the American Educational Research Association (AERA)"--
pt. A. Conceptualizing environmental education as a field of inquiry -- pt. B. Research on environmental education curriculum, learning, and assessment : processes and outcomes -- pt. C. Issues of framing, doing, and assessing in environmental education research.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Environmental education -- Handbooks, manuals, etc; Environmental sciences -- Study and teaching -- Handbooks, manuals, etc; Electronic books